GE_GERICHTE P/8413/2020 vom 6. Oktober 2022 - GE Cour de justice (2022)
SÉJOUR ILLÉGAL;REPRÉSENTATION DE LA VIOLENCE;PORNOGRAPHIE DURE;EXPULSION(DROIT DES ÉTRANGERS);USAGE DE FAUX(DROIT PÉNAL) | CP.135.al1; CP.251.al1; CP.66abis; CP.197.al4; CP.47; CP.49; LEI.115.al1.letb; LEI.118.al1